2020
DOI: 10.3349/ymj.2020.61.5.349
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Pre-Exposure Prophylaxis Adherence among Female Sex Workers

Abstract: Globally and in Africa specifically, female sex workers (FSWs) are at an extraordinarily high risk of contracting human immunodeficiency virus (HIV). Pre-exposure prophylaxis (PrEP) has emerged as an effective and ethical method with which to prevent HIV infection among FSWs. PrEP efficacy is, however, closely linked to adherence, and adherence to PrEP among FSWs is a complex and interrelated process that has been shown to be of importance to public health policies and HIV control and intervention programs. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 64 publications
0
35
3
Order By: Relevance
“…A recent metaanalysis found that anticipated stigma from partners and family, concerns about side effects, and low perceived risk were also salient barriers to PrEP use in this population (Abou Ghayda et al, 2020). Further, several studies have shown that greater knowledge of PrEP is integral to improved uptake among female sex workers (Abou Ghayda et al, 2020). In a qualitative study conducted in Kenya, authors reported that female sex workers expressed an interest in learning about PrEP from other sex workers, illuminating that a peer-model of engagement could be particularly useful for disseminating key information about PrEP and overcoming barriers to clinic-led education (Bazzi et al, 2019).…”
Section: Cisgender Female Sex Workersmentioning
confidence: 99%
See 3 more Smart Citations
“…A recent metaanalysis found that anticipated stigma from partners and family, concerns about side effects, and low perceived risk were also salient barriers to PrEP use in this population (Abou Ghayda et al, 2020). Further, several studies have shown that greater knowledge of PrEP is integral to improved uptake among female sex workers (Abou Ghayda et al, 2020). In a qualitative study conducted in Kenya, authors reported that female sex workers expressed an interest in learning about PrEP from other sex workers, illuminating that a peer-model of engagement could be particularly useful for disseminating key information about PrEP and overcoming barriers to clinic-led education (Bazzi et al, 2019).…”
Section: Cisgender Female Sex Workersmentioning
confidence: 99%
“…In one paper, the authors presented the results of two studies which showed that, among GBMSM, desiring more closeness with a primary partner and believing that condoms interfere with intimacy were independent predictors of PrEP adoption attitudes and behaviors (Gamarel & Golub, 2019). In a second paper (Abou Ghayda et al, 2020), these same authors collected mixed-methods data from 145 HIV-negative GBMSM in primary relationships. They asked participants to report on their sexual health goals and three main goal content categories emerged: HIV/STI prevention, sexual satisfaction, and intimacy.…”
Section: Sexual Satisfactionmentioning
confidence: 99%
See 2 more Smart Citations
“…10 The effectiveness of PrEP, however, is highly dependent on adherence, which has been challenging for many, including sex workers. 12,13 HIVST and PrEP are potentially complementary tools that could be combined to empower sex workers to prevent HIV acquisition, but few studies have jointly evaluated PrEP and HIVST in any setting.…”
Section: Introductionmentioning
confidence: 99%